Fully quantitative X-ray characterisation of Evonik Aeroxide TiO2 P25 (R) - Tobaldi, D. M.
Photocatalysis with TiO2 is one of the most promising methods for combatting environmental pollution. Of commercially available photocatalysts, Evonik Aeroxide (formerly Degussa) P25 (R) titania is probably the most extensively used. In this communication, we quantitatively characterise the full phase composition (both crystalline and amorphous content) of P25, as well as the microstructure of individual phases (crystalline domain size distribution and dislocation density). This was achieved with advanced X-ray diffraction (XRD) methods: Rietveld-RIR and whole powder pattern modelling (WPPM). Quantitative phase analysis (QPA) showed the precise composition of P25 to be 76.3 wt% anatase, 10.6 wt % rutile and 13.0 wt% amorphous, and microstructural details are given for the two crystalline phases. (C) 2014 Elsevier B.V. All rights reserved.